Radiological management of traumatic lymphatic injuries in children - Muhammad S. Khan; Cameron Casson; Genette Bergman; Ali Mokdad; Shellie Josephs; Faisal G. Qureshi (Elsevier, 2021)
Traumatic lymphatic leaks are uncommon in children. Outcomes of conservative treatment are variable with surgery being often necessary. Lymphangiography has been successful in adults. Its utility in children is rarely reported. We report two cases of successful lymphangiographic treatment of traumatic lymphatic leak in children. First patient was a 15-year-old male developed a large right-sided pleural effusion 3 weeks after being physical assaulted. Tube thoracostomy yielded high volume chylous output. After failed conservative, operative and initial radiological interventions, he underwent bilateral femoral lymphangiography demonstrating abnormal ducts with contrast extravasation. This was controlled using coils and cyanoacrylate glue. Second patient was an 8-year-old male who following a road traffic accident underwent surgery for left diaphragmatic rupture. Drain was placed in the retroperitoneum where chylous fluid was observed. Postoperatively, after resuming diet, drains had significant chylous output. Lymphangiogram performed via inguinal nodes demonstrated abnormal right retroperitoneal nodes. The drain was exchanged for a pigtail catheter away from the lymphatics resulting in improved lymphatic flow. Lymphangiography is useful for treatment of traumatic lymphatic leaks in children. It should be considered early when conservative treatments fail. We present current evidence on lymphatic mapping and intervention for lymphatic leaks in children with a proposed algorithm.